Evaluation and comparison of feeds on a combined economic-nutritional basis - Sebastiá, José M.; Bird, Herbert R.; López, Jorge (Pesquisa Agropecuaria Brasileira, 2014)
A procedure for evaluating rations on a combined economic-nutritional basis was developed in the United States using prices of corn and soybean meal to establish cost per unit of energy and protein. Costs of other nutrients were calculated from the price of their most economical source. In Brazil, also, corn and soybean meal are economical sources of energy and protein, and they are more suitable for use at high levels than are the alternative ingredients which are sometimes more economical. Wide price fluctuations in Brazil make it difficult to prepare a table relating corn and soybean meal prices to energy and protein costs. However, simplified equation have been developed to accomphis this. If α = cost of energy and protein in 1 kg of corn and b = cost of energy and protein in 1 kg of soybean meal, the cost of 1,000 kcal of metabolizable energy = 4.9a – b/14.4 and the cost of 1 kg of protein 1.55b – a/0.59. Similar equations could be developed for other sources of energy and protein in countries not using corn or soybean meal. Using these equations with prices prevailing in Porto Alegre, in 1969, it was calculated that energy accounted for 4.9% of the cost of ingredients of a broiler mash, protein 42.2%, minerals 6.5% and vitamins 1.9%.